Design, synthesis and antifungal activity of novel 1,4-benzoxazin-3-one derivatives containing an acylhydrazone moiety - Tang, Chenghao; Guo, Wenbo; Yang, Shengzhou; Hu, Xiuhong; Chen, Xingju; Wang, Xiang (Frontiers in Chemistry, 2023)
A series of 1,4-benzoxazin-3-one derivatives containing an acylhydrazone moiety were designed, synthesized and evaluated for their in vitro antifungal activities against Gibberella zeae, Pellicularia sasakii, Phytophthora infestans, Capsicum wilt, and Phytophthora capsica. The structures of target compounds were characterized by 1 H NMR, 13 H NMR, 19 F NMR and HRMS. The preliminary antifungal evaluation of all target compounds showed that some target compounds possessed moderate to good activities against G. zeae, P. sasakii, P. infestans and C. wilt. Among them, compounds 5l and 5o exhibited noticeable inhibition effects against G. zeae with the EC50 values (effective concentration for 50% activity) of 20.06 and 23.17 μg/mL, respectively, which were even nearly double effective than that of hymexazol (40.51 μg/mL). Meanwhile, compound 5q displayed a notable inhibitory effect toward P. sasakii, with the EC50 value of 26.66 μg/mL, which was better than that of hymexazol (32.77 μg/mL). In addition, compound 5r yielded the EC50 value of 15.37 μg/mL against P. infestans, which was less than those of hymexazol (18.35 μg/mL) and carbendazim (34.41 μg/mL). Eventually, compound 5p showed higher inhibitory effect against C. wilt, with EC50 value of 26.76, which was better than that of hymexazol (> 50 μg/mL).